How is neck dissection performed in Oral and Maxillofacial Surgery? Results of a representative nationwide survey among university and non-university hospitals in Germany - Pabst, Andreas; Thiem, Daniel G.E.; Goetze, Elisabeth; Bartella, Alexander K.; Neuhaus, Michael T.; Hoffmann, Jürgen; Zeller, Alexander N. (Clinical Oral Investigations, 2021)
Introduction: Neck dissection (ND) is a surgical procedure addressing cervical lymph nodes and metastases in patients with oral squamous cell carcinoma (OSCC). The aim of this study was to analyze clinical decisions regarding indications and variations of ND in Oral and Maxillofacial Surgery (OMFS) in Germany. Material and methods: A nationwide survey of the German Association of Oral and Maxillofacial Surgery was performed using dynamic online questionnaires including 38 questions. Data about oncological centers, case numbers, and staging procedures were collected. Relevant aspects, such as inclusion of level IIb and levels IV and V to ND, uni- vs. bilateral ND, and the influence of extra-nodal extension (ENE) of metastases on extension of ND were evaluated. Results: Eighty-four OMFS of university and non-university hospitals participated in the study (responding rate 21.4%). Sixty-six (78.57%) stated to work at certified cancer centers and 53.57% of the hospitals treated between 50 and 100 OSCC cases per year. CT and/or MRI of the head and neck was performed in most of the staging procedures. Level IIb was included by 71 (93.42%) of the participants in selective ND. Levels IV and V were included by 53 (69.74%) in node-positive neck. In solitary ipsilateral metastases (ENE−), 49 participants (62.82%) stated to perform exclusively an ipsilateral ND and 40 (51.95%) stated to perform only an ipsilateral ND in ENE+. Conclusion: This study demonstrated a high rate of certified cancer centers in Germany showing differences regarding staging procedures, indications, and extension of ND, especially in increasingly complex cases. Clinical relevance: Clinical decisions regarding ND are dependent on case-individual aspects and must be decided individually.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Lymph node; Metastases; Neck dissection; Oncology; Oral squamous cell carcinoma; Survey